Length-Weight Relationships and Condition Factors of Tigawaja Fish (Nibea sp.) Landed on PPI Cikidang Pangandaran West Java - Yasinta Anggararatri; Dyahruri Sanjayasari (Journal Omni-Akuatika, 2022)
Tigawaja fish (Nibea sp.) is a demersal fish that is commonly found in Indonesian waters. Tigawaja fish is a white-fleshed fish that contains about 18% protein, 0.03% total fat, vitamin A, niacin, calcium, and sodium. However, there are still few studies that discuss the growth characteristic of Tigawaja fish, hence, the management of Tigawaja fish resources cannot be optimized. Current study aims to determine the relationship between length and weight and condition factors of Tigawaja fish. Data collection was carried out at PPI Cikidang Pangandaran, West Java in February 2021. The field work method used random sampling of fish landed at PPI Cikidang Pangandaran. The parameters measured including the length and weight of the fish, and the data were analyzed descriptively. The results showed that the growth pattern of Tigawaja fish landed at PPI Cikidang Pangandaran was negative allometric with b value at 2.71. Regression analysis of the relationship between length and weight of Tigawaja fish resulted a coefficient of determination R2 of 85.69% indicating a very strong relationship between length and weight of Tigawaja fish. The results of the condition factor values have an average of 1.41 and relative weight with an average of 101.30. The results of the regression analysis of the relationship between condition factors and relative weight resulted a coefficient of determination R2 of 76.18% showed the relationship was very strong.Keywords: Tigawaja fish, length, weight, condition factor, relative weight, PPI Cikidang Pangandaran